The relationship between taxpayer and tax administration and its role in improving tax examination policies (A field study on tax examiners in some of the financial directorates in Syria (Journal of Hama University, 2019)
The study aimed at revealing the transparency of the relationship between the taxpayer and the tax administration and its role in improving tax examination policies by conducting a field study of the tax assessors in some of the Syrian Arab Republic's finances to limit the problems faced by the examiners when examining the files of the taxpayers. May be faced with obstacles both with their management or with the laws and instructions issued to them or with the taxpayers themselves. It was found that the tax assessor faced several problems, in the performance of his duty, and faced with serious difficulties, arising from his presence in the system of work requires him and his colleagues to reach a specific level of proceeds in advance, regardless of what may face the community or some of the activities may affect the entry The tax assessor must balance between the justice when examining the books of the taxpayers and to say the word right, and be fair when assessing the entry of taxpayers to link the tax on this entry. To arrive at the exact outcome .The results of the study showed that there are several problems facing the tax examiner in the performance of his work, the most important of which is the failure of the taxpayers to keep regular books and the lack of adequate training for the examiners. The study confirmed that the problems facing the tax examiner are not impossible.The study also recommended the establishment of a central administration for the dissemination of tax awareness and a high institute for tax training, and the need to focus in subsequent studies on tax policies and the mechanism to develop them.